Lagrangian stochastic model for buoyant gas dispersion in a simple geometric chamber - Kim, Byung-Gu; Kim, Jong Soo; Lee, Changhoon (ELSEVIER SCI LTD, 2009)
A new Lagrangian stochastic model is proposed to predict dispersion of buoyant gases, such as hydrogen, by including the buoyant forcing term in the stochastic model and by considering the wall-plume interaction based on the hydrostatic approximation. The proposed model was validated by carrying out simulations for three accidental hydrogen release scenarios. The simulation for the case of instantaneous release exhibits a realistic spreading of the hydrogen puff in the vicinity of the horizontal ceiling, caused by the hydrostatic pressure. The predicted variation of concentration for the cases of continuous release shows good agreement with other simulation and experimental results. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: TURBULENT FLOWS; HYDROGEN